Quality of life in adults from a rural area in Southern Brazil: a population-based study - Caroline Cardozo Bortolotto; Christian Loret de Mola; Luciana Tovo-Rodrigues (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze the quality of life and its determinants in a population living in a rural area. METHODS This is a population-based, cross-sectional study with individuals aged 18 years or over from the rural area of Pelotas, State of Rio Grande do Sul, Brazil. We evaluated quality of life using the WHOQOL-BREF, which has four domains (physical, psychological, social relations, and environment) and two questions: overall quality of life and satisfaction with health. We considered as independent variables the demographic, socioeconomic, and health variables. We evaluated the associations using linear regression in the four domains and ordinal logistic regression in the two general questions on quality of life and satisfaction with health. RESULTS The sample consisted of 1,479 individuals. The prevalence of the perception of overall very poor quality of life and dissatisfaction with health were 22.5% and 26.3%, respectively. Individuals who were older (p < 0.001), non-white (p = 0.004), with lower education level (p < 0.001), poorer (p = 0.001), and who had always lived in the rural area (p = 0.049) were less likely to have a better perception of overall quality of life. As for satisfaction with health, women (p = 0.001), older individuals (p = 0.001), those unemployed (p = 0.023), and those with diseases were less likely to report higher satisfaction with health. For the four domains evaluated, the results were consistent with those observed for the general questions. CONCLUSIONS The most relevant aspects that negatively defined the quality of life of the population were being a woman, older, non-white, having a low income, having a lower education level, having always lived in the rural area, being unemployed, and having a disease. Given that they are significant factors as determinants of health, these results suggest that quality of life is an issue that should be placed among health needs, especially regarding the most vulnerable groups in rural areas.